Cyclic stability of lithium nitrate trihydrate in plate fin heat exchangers. (October 2020) - Tamraparni, Achutha; Shamberger, Patrick J.; Felts, Jonathan R.
Highlights: Successful integration of lithium nitrate trihydrate (LNH) into a heat exchanger. LNH performance validated over 500 continuous thermal cycles. Results show consistent specific latent heat energy storage of 294 ± 37 J·g −1 . Subcooling temperatures of LNH changed very little for 500 continuous cycles. Abstract: Latent heat thermal energy storage systems based on hydrated salts are effective solutions for thermal management of transient thermal systems. Hydrated salts have relatively large specific and volumetric latent heat compared to paraffin phase change material. However, hydrated salts are not ubiquitous in energy storage systems because they exhibit inconsistent sub-cooling temperatures and tend to phase segregate due to incongruent melting which leads to degradation in the energy storage capacity. Here we demonstrate high stability of a congruently melting salt hydrate - lithium nitrate trihydrate, in a vacuum sealed plate-fin heat exchanger with water as heat transfer medium cycling between 40 °C and 20 °C, over 500 heating and cooling cycles. The specific latent heat of lithium nitrate trihydrate remained stable at 294 ± 37 J·g −1 and the sub-cooling temperatures increased only by 0.27 °C, demonstrating its stability in operational thermal energy storage systems.